Cardiovascular remodeling in patients with diabetic сardiomyopathy - A. S. Veklich; N. A. Koziolova; P. G. Karavaev (Российский кардиологический журнал)
Aim. To assess cardiovascular remodeling in patients with diabetic cardiomyopathy (DCM) and compare  it with healthy individuals.Material and methods. Among outpatients with newly diagnosed type 2 diabetes (T2D), according  to inclusion and exclusion criteria, a group of participants  with diabetic cardiomyopathy (DCM) with left ventricular diastolic dysfunction (LV DD) was made before treatment. The second group consisted of healthy individuals of the  corresponding  age.  The  structural  and  functional  state  of the  heart  was studied using echocardiography and determination of the N-terminal prohormone of the brain natriuretic peptide  (Nt-proBNP) in the blood; of the arteries  — using volume sphygmoplethysmography. Markers  of fibrosis were  determined in the blood:  tissue  inhibitor of matrix metalloproteinase-1 (TIMP-1) and  C-terminal telopeptide  1 (CTP-1).Results. The DMC prevalence in patients with newly diagnosed T2D was 18,7%. LV DD was associated not only with T2D, but also with obesity (r=0,48; p=0,029), blood pressure even in the normal range  ((r=0,42; p=0,031  for systolic blood pressure; (r=0,39; p=0,042) for diastolic blood pressure). The Nt-proBNP levels in the normal range  and  TIMP-1 were  higher  in the  DCM group  compared with the  group  of healthy individuals (p<0,001 and p<0,001, respectively). CTP-1 was lower in the first group compared with the second (p<0,001).  In the DCM group,  a higher cardioankle  vascular  index (CAVI1)  was  recorded compared to  the  group  of healthy individuals (p<0,001).Conclusion. LV DD cannot  be presented as a pathognomonic criterion for DCM. Nt-proBNP levels in the normal range of 76,23+14,47 pg/ml, which do not reach the diagnostic criteria for heart failure, an increase  in TIMP-1 and a decrease in CTP-1can be considered as additional markers  of DCM. Given the fact that two parallel processes occur  during the DCM formation, manifested  by cardiac  and arteries’ remodeling, the CAVI1 can also be considered as an additional DCM marker.